Opportunities and Challenges of Housing Traditional Bali as Supporting Elements of Tourism Village in the Traditional Village of Pengotan, Bangli - Luh Putu Ambaraswati, Ni; Gusti Ngurah Anom Rajendra, I; Ketut Agusintadewi, Ni (ASTONJADRO, 2022)
Traditional settlement patterns are often represented as places that still hold traditional and cultural values in everyday life that are related to beliefs or religions that are special or unique in a particular community rooted in a place outside of historical determination that supports tourist villages. . This research was conducted in Pengotan Village, which has a unique cultural dedication tourism village with traditional Balinese architectural settlements, culture and customs in Pengotan Traditional Village, Bangli. Pengotan Village is a Bali Aga village, one of which still maintains traditional mountain village values using the Tri Angga (Hulu-teben) settlement concept. This study uses a qualitative method with a case study approach. The purpose of this study is to analyze the opportunities for the development of Traditional Village Customary settlements which are supporting elements of a Traditional Village into a Tourism Village, as well as the challenges that occur in a Traditional Village after its development into a Tourism Village.